Upaya Kepala Sekolah Dalam Meningkatkan Mutu Kegiatan Belajar Mengajar di SMPI Integral Luqman Al-Hakim 02 Batam Tahun Pelajaran 2023/2024 - Ferda Agustina (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The quality of education or the quality of KBM in Indonesia is still very low compared to other countries, for that in improving the quality of education in Indonesia, efforts from various parties are needed. These parties other than the government and the community are school principals. Because the principal is a leader in educational institutions, therefore the principal has a very important role in improving the quality of KBM.. The improvement of KBM quality can be measured through several conditions, namely inputs, processes and outputs. Input is the way the school screens prospective students, while the process is a way both teaching and learning in a school led by a teacher (Teaching and Learning Activities), while output is the result of the process. This research has a purpose, namely: to determine the principal's efforts in improving the quality of KBM at SMPI Integral Luqman AL-Hakim 02. Basically, this research is descriptive qualitative, providing a picture or description of a situation as clearly as possible about certain individuals or groups in accordance with actual conditions. The descriptive method is used to analyze qualitative data with data that cannot be realized with numbers. Thus, the results of the study show that the Principal of SMPI Integral Luqman AL-Hakim 02 Batam always strives to improve the quality of KBM in various ways, including always holding or participating in training on the ability to manage KBM, always striving for teachers according to their respective competencies, always providing coaching or motivation to students, always striving for infrastructure and learning media to support KBM, always supervise the running of KBM